2019
DOI: 10.1017/prp.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

Leaving an attacked group: Authoritative criticism decreases ingroup favoritism

Abstract: Research suggests people try to protect their social self-esteem from threats from the ingroup or the outgroup. However, how members react to a threat to social self-esteem from a third party remains unclear. Three studies were conducted to examine the influence of a threat to social self-esteem from an authoritative third party on ingroup favoritism. We explored the effect of negative (versus positive) evaluation from the testing system on explicit and implicit ingroup favoritism in Study 1 and Study 2 respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…These results directly replicated the results of previous studies in which the Chinese participants were also found to be more inclined to cooperate with outgroup members under the minimal group paradigm (Wu et al, 2015, 2016). Similar results were also reported by researches using other tasks under minimal group paradigm (Zuo et al, 2018; Dang et al, 2019). For example, researchers found that East Asian participants allocated more resources to the outgroup members than to ingroup members when there were intragroup competitions within the minimal groups (Zuo et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results directly replicated the results of previous studies in which the Chinese participants were also found to be more inclined to cooperate with outgroup members under the minimal group paradigm (Wu et al, 2015, 2016). Similar results were also reported by researches using other tasks under minimal group paradigm (Zuo et al, 2018; Dang et al, 2019). For example, researchers found that East Asian participants allocated more resources to the outgroup members than to ingroup members when there were intragroup competitions within the minimal groups (Zuo et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…As a functionally coherent disease defense mechanism, the behavioral immune system can generate a series of consistent changes in down-stream perceptual, affective, cognitive, and behavioral processes (Schaller and Neuberg, 2012; Schaller et al, 2015; Murray and Schaller, 2016). Although previous studies have investigated the ingroup derogation phenomenon in East Asian cultures by using many different tasks, such as the face perception task (Jahoda et al, 1972; Zhao et al, 2012; Wu et al, 2016), emotion judgment task (Wu et al, 2016; Xie et al, 2019), memory task (Zhao et al, 2012), trait rating task (Ma-Kellams et al, 2011; Liu et al, 2015), attribution task (Hewstone and Ward, 1985), cooperation and allocation task (Wu et al, 2015, 2016; Zuo et al, 2018; Dang et al, 2019), etc., the current study had only examined the effects of infectious disease on ingroup derogation attitude in the domain of cooperation. If ingroup derogation is indeed an evolutionarily based disease defense mechanism, its activation should result in other functionally related changes, such as altered attention and avoidance response to threat-related targets (e.g., Miller and Maner, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the differing effects of similarity and interaction on group judgments found in our research reveal one core difference between the two perspectives. The polarizing effect of similarity on warmth and competence judgments is in line with the inference that similarity produces a categorybased process (Brewer & Harasty, 1996;Dang et al, 2019;Hamilton et al, 2004), while the polarized warmth and enhanced competence judgments reflect a goal-based process, which is induced by interaction (Newheiser & Dovidio, 2015;Stroessner & Dweck, 2015). Therefore, the current research indicates that the route that group formation (based on shared traits or shared goals) takes determines the (trait-based or goalbased) process of group information, which then engenders different group judgments.…”
Section: Discussionsupporting
confidence: 69%
“…Devaluation context. Drawing on Dang et al (2019), devaluation was operationalized by providing participants with a poor evaluation of their own group's performance. Participants were told that they would form a group with another three participants on our online platform and then complete some tasks together concerning group decision-making.…”
Section: Methodsmentioning
confidence: 99%